Incorporating food addiction into disordered eating: the disordered eating food addiction nutrition guide (DEFANG) - Wiss, David A. (Eat Weight Disord, 2016)
Although not formally recognized by the DSM-5, food addiction (FA) has been well described in the scientific literature. FA has emerged as a clinical entity that is recognized within the spectrum of disordered eating, particularly in patients with bulimia nervosa, binge-eating disorder and/or co-occurring addictive disorders and obesity. Integrating the concept of FA into the scope of disordered eating has been challenging for ED treatment professionals, since there is no well-accepted treatment model. The confusion surrounding the implications of FA, as well as the impact of the contemporary Westernized diet, may contribute to poor treatment outcomes. The purpose of this review is twofold. The first is to briefly explore the relationships between EDs and addictions, and the second is to propose a new model of conceptualizing and treating EDs that incorporates recent data on FA. Since treatment for EDs should vary based on individual assessment and diagnosis, the Disordered Eating Food Addiction Nutrition Guide (DEFANG) is presented as a tool for framing treatment goals and helping patients achieve sustainable recovery.